Argyrophilic nucleolar organizer regions (AgNORs) in odontogenic myxoma (OM) and ameloblastic fibroma (AF) - Martins, Cristiane; Carvalho, Yasmin Rodarte [UNESP]; Vieira Do Carmo, Maria Auxiliadora (Wiley, 2001)
Ten cases of odontogenic myxoma (OM) and six cases of ameloblastic fibroma (AF) were subjected to comparative analysis by the AgNOR technique, in order to determine a possible difference in cell proliferation index between these lesions. The mean AgNOR number of the mesenchymal component of AF was compared with its epithelial component and the difference was not found to be statistically significant. The mean AgNOR index of the AF group was significantly higher than that of the OM group. Moreover, the mesenchymal component of AF demonstrated increased AgNOR numbers compared with that of OM (P<0.05). These results suggest that the epithelial and mesenchymal components of AF may have similar cell proliferative activity. However, the cell proliferative index of this lesion seems to be higher than that of OM.
Keywords: Ameloblastic fibroma; Argyrophilic nucleolar organizer regions (AgNORs); Odontogenic myxoma; cell division; chromosome NOR; comparative study; epithelium; human; mesoderm; nonparametric test; observer variation; odontogenic tumor; pathology; silver staining; ultrastructure; Cell Division; Epithelium; Humans; Mesoderm; Nucleolus Organizer Region; Observer Variation; Odontogenic Tumors; Silver Staining; Statistics, Nonparametric